2017
DOI: 10.1109/tps.2017.2697941
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Design of Linear Induction and Synchronous Motors for Electromagnetic Launch of Civil Aircraft

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk This article has been accepted for inclusion in a future issue of this journal. Content is final as presented, with the excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As the laminated structure is used in AFPMSMs for eddy current reduction, the principle of eddy current at the core is presented in this section. The eddy current loss is affected by the total length of the eddy current loop, as shown in Equation (1) where Pe is the eddy current loss, k is the conductivity, t is the thickness of the conductor passing through, f is the frequency, and Bm is the maximum magnetic flux density. As described in Equation ( 1), the eddy current loss is proportional to the square of the thickness of the conductor.…”
Section: Principle Of Eddy Current Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…As the laminated structure is used in AFPMSMs for eddy current reduction, the principle of eddy current at the core is presented in this section. The eddy current loss is affected by the total length of the eddy current loop, as shown in Equation (1) where Pe is the eddy current loss, k is the conductivity, t is the thickness of the conductor passing through, f is the frequency, and Bm is the maximum magnetic flux density. As described in Equation ( 1), the eddy current loss is proportional to the square of the thickness of the conductor.…”
Section: Principle Of Eddy Current Lossmentioning
confidence: 99%
“…Most AC machine drive systems applied to aircraft, automotive, and industry are built with permanent magnet and induction machines. Induction motors (IM) have been widely used in industry and propulsion systems applied in aircrafts [1][2][3]. It has also been indicated that a water pump, considered a heart part of the irrigation system, has been built with IM.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods allow a very fast computation of working temperatures [1,3,4,15,16], so they are the way to go if iterative optimization methods are employed. As a reference, Bertola et al [20], computed the transient thermal behavior of a linear permanent-magnet machine and a linear induction machine for electromagnetic launch systems. The computation was based on simple formulations, which allowed the authors to evaluate the temperature rise of the machines under different current density values.…”
Section: Introductionmentioning
confidence: 99%
“…In precision manufacturing, there are stricter demands for linear motors, such as those regarding thrust density and thrust fluctuation. Besides structural improvements, increasing the armature density of the motor is the most effective way to increase the thrust density [1][2][3][4][5]. However, the temperature rise that is caused by the excessive electrical density is also an unacceptable problem in the precision field [6,7].…”
Section: Introductionmentioning
confidence: 99%